'I've been as intimate with him as I have been with anybody': queer approaches, encounters and exchanges as live art performer training. Issue 2 (2nd April 2020) - Sellars, Kieran
Abstract : Considering Live Art's resistance to conventional structures of power and performance practices, this article argues that Live Art affords more egalitarian modes of training to emerge. Focusing specifically on the cross-generational artistic exchange between performance artists, Martin O'Brien and Sheree Rose, it is this article's contention that it is through peer-mentorship and not a one-directional form of master-led training, that knowledge can be seen to be shared and nurtured. With their generous, egalitarian and familial approach, O'Brien and Rose offer multilateral opportunities to train the body beyond the confines of conventional heteronormative training paradigms. Considering O'Brien and Rose's engagement with BDSM practices in their performances, this article highlights how a different kind of discipline, generosity and training can develop alternative opportunities to train the body and disseminate knowledge. Thus, this article repositions perceptions of preparation and structure within discourses and practices of Live Art. By both engaging with and beyond texts and discourses on psychophysical performer training and queerness, this article theorises a departure from the phallocentric privileging that is evident in some of the performer trainings, performance practices and processes developed in the latter half of the twentieth century.